Indian Stock Market A Study on Recent Development - Arun Lawrence and Shijina A. S (REVIEW OF SOCIAL SCIENCES, 2013)
The origin of the stock market in India goes back to the end of the eighteenth century when long-term negotiable securities were first issued. However, for all practical purposes, the real beginning occurred in the middle of the nineteenth century after the enactment of the companies Act in 1850, which introduced the features of limited liability and generated investor interest in corporate securities. An important early event in the development of the stock market in India was the formation of the native share and stock brokers ‘Association at Bombay in 1875, the precursor of the present day Bombay Stock Exchange. In stock market, share prices rise and fall depending, largely, on market forces. Share prices tend to rise or remain stable when companies and the economy in general show signs of stability and growth. An economic recession, depression, or financial crisis could eventually lead to a stock market crash. The government of India introduced many schemes and agencies, to attract investors in stock market and to protect the interest of investors in stock market. Now, the market features a developed regulatory mechanism and a modern market infrastructure with growing market capitalization, market liquidity, and mobilization of resources